2004
DOI: 10.1038/nature02971
|View full text |Cite
|
Sign up to set email alerts
|

Jarosite as an indicator of water-limited chemical weathering on Mars

Abstract: The Mars Exploration Rover Opportunity identified the ferric sulphate mineral jarosite and possible relicts of gypsum at the Meridiani Planum landing site. On Earth, jarosite has been found to form in acid mine drainage environments, during the oxidation of sulphide minerals, and during alteration of volcanic rocks by acidic, sulphur-rich fluids near volcanic vents. Jarosite formation is thus thought to require a wet, oxidizing and acidic environment. But jarosite on Earth only persists over geologically relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(86 citation statements)
references
References 25 publications
0
85
0
1
Order By: Relevance
“…Noachian and Hesperian terrains are well preserved and widespread on Mars (Michalski et al, 2013). Jarosite is preserved for geological timescales only in extremely arid conditions, and the persistence of jarosite on Mars is testament to the planet's extreme surface aridity in post-Hesperian times (Elwood Madden et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Noachian and Hesperian terrains are well preserved and widespread on Mars (Michalski et al, 2013). Jarosite is preserved for geological timescales only in extremely arid conditions, and the persistence of jarosite on Mars is testament to the planet's extreme surface aridity in post-Hesperian times (Elwood Madden et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…However, such extrapolations depend upon the pH of weathering (Fig. 2) and such pH is poorly constrained on Mars: weathering pH may have been very acidic (Elwood Madden et al, 2004;Klingelhofer et al, 2004;Tosca et al, 2004;Hurowitz et al, 2006) or close to neutral Bibring et al, 2006). The pH of a weathering solution strongly affects relative mineral persistences (Fig.…”
Section: Mineral Persistencementioning
confidence: 99%
“…(http://www.news.cornell.edu/releases/rover/Mars.jarosite.html) Recent studies have identified iron sulphate minerals on Mars [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%